2018
DOI: 10.1002/ejp.1297
|View full text |Cite
|
Sign up to set email alerts
|

European Pain Federation (EFIC) position paper on appropriate use of cannabis‐based medicines and medical cannabis for chronic pain management

Abstract: This position paper provides expert recommendations for nonspecialist and specialist healthcare professionals in Europe, on the importance and the appropriate use of cannabis-based medicines as part of a multidisciplinary approach to pain management, in properly selected and supervised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 101 publications
(123 reference statements)
1
114
0
19
Order By: Relevance
“…71 The European Pain Federation has published a position paper about the appropriate use of cannabis-based medicines and medical cannabis for chronic pain management. Key points are that: 1) current evidence is insufficient to state whether cannabis-based medicines and medical cannabis differ in their efficacy, tolerability and safety; 2) cannabis-based medicines can be considered as third-line therapy for chronic neuropathic pain; 3) THC:CBD oromucosal spray (nabiximols) can be considered as part of an add-on individual therapeutic trial for individuals with cancer pain who have inadequate pain relief from opioids or other established analgesics, 72 although evidence for this latter recommendation is limited.…”
Section: Cannabinoids For Pain Managementmentioning
confidence: 99%
“…71 The European Pain Federation has published a position paper about the appropriate use of cannabis-based medicines and medical cannabis for chronic pain management. Key points are that: 1) current evidence is insufficient to state whether cannabis-based medicines and medical cannabis differ in their efficacy, tolerability and safety; 2) cannabis-based medicines can be considered as third-line therapy for chronic neuropathic pain; 3) THC:CBD oromucosal spray (nabiximols) can be considered as part of an add-on individual therapeutic trial for individuals with cancer pain who have inadequate pain relief from opioids or other established analgesics, 72 although evidence for this latter recommendation is limited.…”
Section: Cannabinoids For Pain Managementmentioning
confidence: 99%
“…Initially, we expected marijuana use to be associated with pain as chronic pain is one of the leading reasons for starting medical marijuana. 37 Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLWH may engage in risky drinking, in order to manage physical pain. 38 A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLWH.…”
Section: Substance Usementioning
confidence: 83%
“…registries is the prevalent use of cannabinoid medicines to treat chronic pain, 17,18,20 despite the limited RCT evidence for use in this indication. 24 Harmonisation of standard data collected is necessary to pool data from various registries internationally. 10 However, RWD obtained from registries does not provide conclusive evidence of efficacy or effectiveness for the same reasons as observational studies of harms arising from recreational use, namely, the challenges in ruling out residual confounding.…”
Section: United Kingdom 19mentioning
confidence: 99%